Public Service Governance And Accountability: A Reform - Raesalat, Riksa; Nurbudiwati, Nurbudiwati; Hanifah, Hani Siti; Tenaesah, Erna Siti; Oroji, Ahmad Muhammad (Perhimpunan Intelektual Muslim Indonesia, 2024)
The research aims to describe the governance and accountability of public services during a reform by taking the research object in Indonesia. The research uses qualitative methods which help describe and understand the substance of an event by strengthening it through phenomenological methods to analyze the same symptoms with different views and a historical approach based on sources of knowledge that occurred in the past. Sources of data from several literature include the Al-Qur'an, al-Hadith, books and journals that are relevant to the research. The data analysis technique uses triangulation as a strategy used to validate data from data sources and themes in a coherent manner. The results of this research recommend that the discussion of public services be related to public services, the public sector and service provision or service delivery which refers to activities and services carried out to meet the needs of the general public. Implementation of service duties and supervision of public services through the system implemented by the state results in poor public services to the community. In an Islamic perspective, the actualization of the application of the Islamic system in aspects of public services will create a bureaucracy that is simple, easy and efficient, responds quickly with the ability and capability to handle people's affairs. Likewise, fulfilling other public needs such as education, health and so on comes from efficient and effective management of natural resources. It is this reform that will ensure the true welfare of society.